Analisis Etos Kerja Dewan Pengawas Syariah (DPS) Terhadap Pengawasan Produk Deposito Dan Rahn di Bank Muamalat Cabang Sumbawa - Feri Irawan (PT FORMOSA CENDEKIA GLOBAL, 2022)
This research is a field research using qualitative methods and literature review (Library Research). The data used in this study: (1) Primary data was obtained through interviews with the Sharia Supervisory Board, Funding Officer, Customer Service, Teller and Pawn Staff, Head of General and Personnel Division. (2) Secondary data is obtained from books and journals related to research problems. After the data obtained in the field through interviews are collected and then analyzed using a qualitative descriptive method (a form of description of the subject being observed) then the discussion is concluded deductively, namely drawing conclusions from general questions to specific questions. The results of the study found that (1) the Supervision Mechanism of the Sharia Supervisory Board at Bank Muamalat Cab. Sumbawa has carried out its duties according to the mechanism of the Sharia Banking Law No. 21 of 2008 concerning Sharia Banking Chapter V part three article 32 paragraph 3 and Bank Indonesia Circular No. 15/22 DPbs Jakarta, 27 July 2013 (2) Practice of supervision of the Sharia Supervisory Board at Bank Muamalat Cab. Sumbawa on Deposit and Rahn products in terms of supervision in Sharia Management that supervision carried out by DPS rights has limited authority this is not in accordance with the concept of supervision in sharia management that good supervision is carried out by a leader who has the authority to determine policies while supervision is carried out DPS does not have the right and authority as a leader.